Epicatechin product of Camellia sinensis leaves detection by thin layer chromatography and high performance liquid chromatography - Ruaa mohammed ibrahim; Zahraa Suhail Nassir (College of Pharmacy University of Baghdad, 2022)
The current study performed in order to detect and quantify epicatechin in two tea samples of Camellia sinensis (black and green tea) by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Extraction of epicatechin from black and green tea was done by using two different methods: maceration (cold extraction method) and decoction (hot extraction method). Qualitative and quantitative determinations of epicatechin in two tea samples were investigated. Epicatechin identification was made by utilizing preliminary chemical tests and TLC. This identification was also boosted by HPLC and then quantified epicatechin in all ethyl acetate fractions of two tea samples. This research revealed the existence of epicatechin in black and green tea according to TLC and HPLC. The 50% aqueous ethanol was better solvent for extraction of epicatechin from leaves of tea. Quantitative estimation of epicatechin by HPLC revealed that ethyl acetate fraction of DGTAE contains the higher concentration of epicatechin than other analyzed fractions. Conclusion, tea is an excellent source of catechins particularly epicatechin that possessed various pharmacological effects.